2013
DOI: 10.1371/journal.pone.0079874
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Transcriptional Fidelity of Patient-Derived Colon Cancer Xenografts in Immune-Deficient Mice

Abstract: Xenografts of human colorectal cancer (CRC) in immune-deficient mice have great potential for accelerating the study of tumor biology and therapy. We evaluated xenografts established in NOD/scid/IL2Rγ-null mice from the primary or metastatic tumors of 27 patients with CRC to estimate their capacity for expanding tumor cells for in vitro studies and to assess how faithfully they recapitulated the transcriptional profile of their parental tumors. RNA-seq analysis of parental human CRC tumors and their derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…The preservation of phenotype and genotype, displayed by PDX models (11), is vital to the development of new antineoplastics, not least in the age of targeted therapeutics (4,36). Similar to Perez-Soler and colleagues (9), tissue architecture was well maintained in our NSCLC samples.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The preservation of phenotype and genotype, displayed by PDX models (11), is vital to the development of new antineoplastics, not least in the age of targeted therapeutics (4,36). Similar to Perez-Soler and colleagues (9), tissue architecture was well maintained in our NSCLC samples.…”
Section: Discussionsupporting
confidence: 75%
“…Xenografts directly established from human tumors have tissue architecture and phenotype more closely resembling that of pancreatic (8), NSCLC (9,10), and colorectal (11) cancers. Expansion of patient-derived tumors in vivo can provide material at early passage for ex vivo assays, such as the clonogenic assay, which show promising correlation between drug response ex vivo and that seen in the patient (12) but is not amenable to highthroughput screening.…”
Section: Introductionmentioning
confidence: 99%
“…Athough both stromal and immune components are replaced over time by murine analogues, the haematopoietic elements show important differences in their spatial distribution 167 or may be missing overall 156,168 . This affects the signal received from molecular profiling, and could require application of specific algorithms for signal correction to avoid or reduce artefacts and biases 156,169 .…”
Section: Main Objectivesmentioning
confidence: 99%
“…Prior studies (5, 7, 8, 25) suggested that the time frame for total murine stroma replacement occurs early after implantation. A study showed that the human blood vessels supporting one human CRC xenograft growth were replaced by the host murine cells by ~3 weeks post-implantation (26); another study suggested that murine endothelial cells completely supported the growth of the PDX by 30 days post-implantation (8).…”
Section: Discussionmentioning
confidence: 99%